Türk siyasal hayatında bir karizmatik lider örneği : Turgut Özal - Keskin, Yakup (My University, 2002)
Bu çalışmanın amacı, Türk siyasal hayatının liderlerinden olan Turgut Özal'ın karizmatik liderlik özelliklerinin incelenmesidir. Çalışmamızın birinci bölümde öncelikle liderlik tanımlanmaya çalışılmış sonra liderin ortaya çıkışı, fonksiyonları, liderliğin özellikleri ve liderlik kuramları incelenmiştir. Liderlik üzerine yapılan bu analizlerden sonra otorite kavramı üzerinde durulmuştur. Otoritenin dayanaklarını inceleyen Max Weber, üç otorite tipinden söz etmektedir. Geleneksel, yasal ve karizmatik otorite. Şüphesiz bunlardan en ilginç olanı olağanüstü yeteneklere veya kişilik özelliklerine dayanan karizmatik otoritedir. Tezimizde Max Weber'in otorite tiplerinden karizmatik otoritenin özellikleri ayrıntılı olarak anlatılmaya çalışılmıştır. İkinci bölümde genel olarak II.Meşrutiyet'ten günümüze Türkiye'nin siyasal, ekonomik ve sosyal olayları değerlendirilmiştir. Turgut Özal'ın hayatı liderlik ve kişilik özellikleri ön plana alınarak anlatılmıştır. Üçüncü bölümde ise liderlik kuramları açısından Turgut özal değerlendirildikten sonra Max Weber'in karizmatik lider kavramının özellikleri ile Turgut Özal'ın liderlik özellikleri karşılaştırılmıştır. Turgut Özal'ın 1980'lerde başlayan yükselişi Max Weber'in karizmatik otorite/ lider yaklaşımı ile önemli benzerlikler göstermektedir. Özal, Türkiye'de yaşanan 1978-80 krizi sonucunda ön plana çıkan, krizin çözülmesi için devrim sayılabilecek nitelikte değişiklikler yapan ve alışılmış siyasetçi tavrının dışında davranan bir lider olmuştur. Krizin bitmesiyle gücü azalan Özal, uygulanan değişim programının tıkanması ile birlikte de İkinci Değişim Programını hazırlayarak sırf taşıdığı misyona dayanarak halkın karşısına çıkmayı düşünmüştür.

This study aimed to investigate the charismatic characteristics of The President Turgut Özal one of the leaders of the Turkish Political Life. At the first section of the study it has been tried firstly to make a definition of the Leadership and then the way of coming out of a leader, its functions, its features and lately researched the theory of the leadership respectively. After this analyze on the leadership it has been focused on the subject 'Authority'. Max Weber the scientist who researched the basis of the authority had mentioned of three types of the authorities which those are Traditional, Legal and Charismatic. Undoubtedly the most interesting one among them is the Charismatic Authority which based on extraordinary characteristics of a personality. In this my thesis it has been tried to explain the Charismatic Authority from those authority types of Max Weber's in a detailed manner. In the second section it has been generally evaluated The economical, social and political events of Turkey starting from the time of the second declaration of the Constitutional Monarchy in the time of The Ottoman Empire. The life of President Turgut Özal has been described with preceding his leadership and personality. Last stage of this preparation explains the comparison between the charismatic Leadership description of Max Weber and The characteristics of the leadership of The President Turgut Özal. The rise of The President Turgut Özal starting from 1980's shows an important relation with the theoretical approach of Max Weber's Charismatic Authority and Leadership thesis. Mr.Özal has become a leader after the crisis occurred in Turkey for the period of time 1978-80 so-called undemocratic time and in order to solve the crisis he was the person who made some revolutionary measures and behaved as unusual politician compared with the others. After the smoothing the effect of the crisis Mr.Özal lost a part of his political force and have being plugged his implemented Transformation Program so having planned a second Transformation Program Mr.Özal carrying his mission wanted to go to a new election.
Keywords: Siaysai Liderler-Turgut Özal; Siyaset Türkiye